The decision of pregnancy termination according to Maqasid al-Shariah and clinical guidelines: case dilemma series - Shalihin, Mohd Shaiful Ehsan; Harun, Zulkifli; Emmaculcate Tiko, Victoria (IIUM Press, 2022)
Termination of pregnancy (TOP) is performed for the sake of saving the life of a pregnant woman in the best clinical judgement of the treating doctor. It is in line with the recommendation in the Qur‟an and by the expert opinion of Islamic and Medical scholars. However, this could be a dilemma for most medical doctors to agree with a TOP request by a pregnant mother in emotional distress due to unplanned pregnancy or premarital conception, which is a grey area for this procedure. This case series aims to highlight this issue. Two related cases of mothers who had features of depression secondary to unplanned and unwanted pregnancy will be discussed. Both mothers requested TOP exhibit traits of hopelessness, sadness, anhedonia, reduced appetite and sleep, feeling low and down. These cases were not recommended for TOP in a tertiary centre. However, these cases were approached with a motivational interview and psychological support in which close follow up had been done at the primary care level. The first mother benefited from counselling and managed well with some antidepressants and psychotherapy. The involvement of family support and open discussion also aided the mother to recover from her acute stress condition and decided to take care of the pregnancy compared to proceeding with TOP. Another case was referred for TOP after adequate assessment because of worsening emotional distress. However, the request was denied, and the mother was sent to Obstetric for follow-up. Furthermore, the mother performed self-abortion, which resulted in sepsis. The need for TOP in psychological distress is still debatable. Monitoring and follow up in primary care settings have become important assisting tools in managing these cases. These tools provide ample time for the mother and doctors to fully understand the situation before deciding to terminate the foetus‟ life, which might not be necessary. However, failure to look at the case from the “Maqāṣid al-Sharīʻah” concept of preservation of life (Hifz al-Nafs) and mind (Hifz al-‘Aql) will lead to unnecessary patient action and jeopardise their lives.